Ethnobotanical knowledge of wild edible and medicinal plants in Southern Morocco: The case of Guelmim Province - Atouife, Soumaya; Essiah, Seloua; Naciri, Kaoutar; Kalili, Adil; Elebiyad, Jamila; El Habazi, Abdellah; Belhasen, Rekia (Ethnobotany Research and Applications, 2026)
Background: In Morocco, Wild edible plants (WEPs) constitute an essential element of traditional knowledge, contributing to food security, healthcare, and cultural heritage. However, their use is declining due to modernization, agricultural intensification, and the loss of local knowledge, highlighting the need for documentation. Methods: An ethnobotanical survey was conducted from August 2024 to August 2025 in Guelmim Province, Southern Morocco. The study covered Guelmim city and three rural communes: Timoulay, Laqsabi Tagoust, and Tighmert. Ethnobotanical Data were collected using semi-structured interviews and focus group discussions with local informants and analyzed using descriptive statistics and quantitative ethnobotanical indices, namely the Fidelity Level (FL), Relative Frequency of Citation (RFC) and Informant Consensus Factor (ICF). Results: A total of 36 wild edible plant species were recorded. The most dominant families are Asteraceae, Fabaceae, and Lamiaceae (8% each). The study revealed a diversity of uses, with leaves (29.09%) predominating for medicinal purposes, followed by fruits (7.27%) and seeds (5.45%). Decoction was identified as the most common preparation method (38.1%). FL ranged from 18.45% to 96.67%, and RFC values varied from 0.21 to 0.86, indicating variable use importance across species, while the ICF values showed overall high informant consensus. Conclusions: The present study highlighted that the people of Guelmim Province possess valuable traditional knowledge Documentation of this heritage can support biodiversity conservation, dietary diversification, and food security. Moreover, providing a foundation for sustainable agricultural practices, notably organic farming. Keywords: Wild edible plants; Ethnobotany; Traditional knowledge; Food security; Guelmim Province; Morocco.